What Does the Value of Science Depend On? - Jankauskas, Skirmantas (Problemos, 1983)
The evolution of positivism resulted in the problem of scientific progress. As the narrow approach to science hindered the solution of this problem, there arose some doubts concerning the cognitive value of science. It was P. Feyerabend who was to go as far as to doubt the value of science in general. He concluded that at present the place taken by science in society does not conform to its value. He suggested separating science from the State. In the historical reconstruction of the question it occurs that the stand taken by P. Feyerabend is based on imaginary conflict between values and scientific approaches. It is pointed out, however, that the problem put forward by P. Feyerabend is of actual importance: it expresses deficiency of cultural interpretation of science.